Correlation between balance, speed, and walking ability in individuals with chronic hemiparesis - Heloisa Maria Jácome de Sousa Britto; Luciana de Andrade Mendes; Cínthia de Carvalho Moreno; Emília Márcia Gomes de Souza e Silva; Ana Raquel Rodrigues Lindquist
Abstract Alterations in balance and gait are frequently present in patients with hemiparesis. This study aimed at determining whether there is a correlation between static and functional balance, gait speed and walking capacity. To that end, 17 individuals with chronic hemiparesis of both sexes (58.8% men and 42.25 women), mean age of 56.3 ± 9.73 years, took part in the study. Static balance was assessed by computerized baropodometry, under two different sensory conditions: eyes open (EO) and eyes closed (EC). Functional balance was evaluated by Berg Balance Scale and walking ability by the Functional Ambulation Classification. Gait speed was assessed by kinemetry. The Kolmogorov-Smirnov test was used to verify data distribution normality. Parametric variables were correlated by Pearson's test and their non-parametric parameters by Spearman's test. Functional balance showed a positive correlation with gait speed (p=0.005; r=0.64) and walking ability (p = 0.019; r = 0.56). Anteroposterior (AP) and mediolateral (ML) alterations with EO and EC exhibited negative correlations with gait speed (EO: AP amplitude (p = 0.0049 and r = -0.48); mean ML deviation (p = 0.019 and r =-0.56)/ EC: mean AP deviation (p = 0.018 and r = -0.56) and mean ML deviation (p = 0.032 and r = -0.52); AP amplitude (p = 0.014 and r = -0.57) and ML amplitude (p = 0.032 and r = -0.52); postural instability (p = 0.019 and r = -0.55)) and walking ability (EO: mean AP deviation (p = 0.05 and r = -0.47) and AP amplitude (p = 0.024 and r = -0.54)). The results suggest correlations between static and functional balance and gait speed and walking ability, and that balance training can be an important component of gait recovery protocols.